Climate Change: How is the Adaptation of Public Health Services? Case Studies in the City of Padang. (November 2019) - Sari, Putri Nilam; Djafri, Defriman; Gusti, Aria
Abstract: Although the implications of climate change for public health continue to be explained, Indonesia still needs a lot of work to guide the development of comprehensive strategies to support health system adaptation. Existing regulations have not been able to increase the participation of Public Health Centers (PHCs) as first-level services to reduce problems that will arise due to the climate. The purpose of this paper is to see the extent of adaptation by PHCs to deal with climate change. This research was carried out by observing the indicators of the adaptation of the PHCs, in-depth interviews and review of related documents in three PHCs. The finding indicates that adaptation activities that need to be improved by PHCs are early warning systems about drought risk, collaboration with institutions concerned with climate change, and participation in reducing greenhouse gas emissions by using a pro-environment transportation system. In conclusion, the adaptation systems of PHCs have begun to be good, but there is no special attention to the risk of climate change that will be increasing in the future.